Probiotic Escherichia coli Nissle 1917 Expressing Elafin Protects Against Inflammation and Restores the Gut Microbiota - Teng, Guigen; Liu, Zilin; Liu, Yun; Wu, Ting; Dai, Yun; Wang, Huahong; Wang, Weihong (Frontiers in Microbiology, 2022)
Intestinal mucosal inflammation and epithelial barrier dysfunction have been implicated as pathological factors in inflammatory bowel disease (IBD). An emerging area of IBD research focuses on probiotics. The probiotic Escherichia coli Nissle 1917 (EcN) is an excellent choice for engineering therapeutic microbes. Elafin is an endogenous specific inhibitor of neutrophil elastase (NE) and proteinase 3, and we previously found Elafin can effectively suppress the development of colitis. Here, we genetically engineered EcN to deliver Elafin (EcN-Elafin) directly to the colonic mucosa and explored the protective effects of EcN-Elafin against colitis in mice. EcN-Elafin significantly alleviated dextran sodium sulfate (DSS) induced colitis. Compared with wild-type EcN, oral administration of EcN-Elafin displayed better effects on loss of weight, colon length shortening, elevated expression of myeloperoxidase (MPO) and proinﬂammatory cytokines and chemokine in colonic tissues. In addition, EcN-Elafin restored the expression and distribution of tight junction protein ZO-1 in colonic tissues back to normal. In a damaged colonic epithelial model utilizing Caco-2 cells stimulated with TNF-α, EcN-Elafin efficiently down-regulated the activation level of NF-κB signaling. EcN-Elafin was also found to have restored the dysbiosis in gut caused by DSS administration. Moreover, EcN-Elafin significantly enhanced the concentrations of butyrate and valerate in the gut lumen. Thus, our findings demonstrated that EcN-Elafin enhanced the colonic epithelial barrier, promoted the resolution of inflammation, modulated the gut microbiota and elevated concentrations of short-chain fatty acids (SCFAs) in the gut. EcN-Elafin may be a potential therapeutic method for IBD.